2020
DOI: 10.1021/acs.est.9b06177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonthermal Plasma on Microstructure and Oxidation Characteristics of Particulate Matter

Abstract: To investigate the effect of nonthermal plasma (NTP) on the microstructure and oxidation characteristics of particulate matter (PM) from diesel engines at different oxidation stages, a self-designed NTP reactor was used to conduct a timevarying oxidation test on PM samples. The oxidized PM samples were analyzed via thermogravimetric analysis and Raman spectroscopy. The results indicated that the effect of NTP could allow the elemental carbon (EC) to more easily start ignition. The oxidation activity of the EC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
4
16
0
Order By: Relevance
“…This was explained by the partial diesel soot oxidation on the DPM's surface, DPM mainly consisting of VOC, which has a higher tendency to be oxidized by free radicals in comparison to carbon in the soot, and resulted in a decreased particle diameter. 41,43 Ji et al 39 reported the alteration of the DPM microstructure from a large aggregate and longer chain structure into a smaller aggregate and shorter chain, which is consistent with the results shown in Figure 3.…”
Section: Sed(j/l)supporting
confidence: 88%
See 3 more Smart Citations
“…This was explained by the partial diesel soot oxidation on the DPM's surface, DPM mainly consisting of VOC, which has a higher tendency to be oxidized by free radicals in comparison to carbon in the soot, and resulted in a decreased particle diameter. 41,43 Ji et al 39 reported the alteration of the DPM microstructure from a large aggregate and longer chain structure into a smaller aggregate and shorter chain, which is consistent with the results shown in Figure 3.…”
Section: Sed(j/l)supporting
confidence: 88%
“…However, the mass oxidation profiles (Figure 5A) indicated a shifting toward a higher temperature, which suggested less DPM reactivity. With the limited available quantity of highly reactive free radicals generated and the gas resident time within the reactor (governed by GHSV), this time-varying soot oxidation phenomenon was experimentally confirmed by 39 using indirect soot oxidation with NTP-induced O 3 , and it was reported that the VOC/EC ratio was higher for diesel soot under treatment at a relatively short duration (<5 min) and VOC was the first to be oxidized by HVD-generated radical species (mainly O 3 ).…”
Section: Sed(j/l)mentioning
confidence: 86%
See 2 more Smart Citations
“…The effects of NTP on PM microstructure under different loads were investigated by Gao et al [20,21] The results showed that the PM oxidation by NTP first occurred on the particle surface, and the lattice arrangement of the particles was more compact after the NTP treatment. Ji et al [22] investigated the effect of NTP on PM oxidation using Raman spectroscopy and thermogravimetric analysis (TGA). The results showed that the oxidation activity of EC was directly affected by the NTP treatment.…”
Section: Introductionmentioning
confidence: 99%